﻿Species delimitation, biogeography, and natural history of dwarf funnel web spiders (Mygalomorphae, Hexurellidae, Hexurella) from the United States / Mexico borderlands - Rodrigo Monjaraz-Ruedas; Raymond Wyatt Mendez; Marshal Hedin (ZooKeys, 2023)
The rarely encountered spider genus Hexurella Gertsch & Platnick, 1979 includes some of the smallest mygalomorph spiders in the world, with four poorly known taxa from central and southeastern montane Arizona, southern California, and northern Baja California Norte. At time of description the genus was known from fewer than 20 individuals, with sparse natural history information suggesting a vagrant, web-building, litter-dwelling natural history. Here the first published taxonomic and natural history information for this taxon is provided in more than 50 years, working from extensive new geographic sampling, consideration of male and female morphology, and sequence capture-based nuclear phylogenomics and mitogenomics. Several new species are easily diagnosed based on distinctive male morphologies, while a complex of populations from central and northern Arizona required an integrative combination of genomic algorithmic species delimitation analyses and morphological study. Four new species are described, including H. ephedra sp. nov., H. uwiiltil sp. nov., H. xerica sp. nov., and H. zas sp. nov. Females of H. encina Gertsch & Platnick, 1979 are also described for the first time. It is predicted that additional new species will ultimately be found in the mountains of central and northwestern Arizona, northern mainland Mexico, and the Mojave Desert of California.